CONCEPTUAL SCHEME SYSTEM FOR MODELING OF TACTICAL SITUATION ON THE BASIS OF GEOINFORMATION SYSTEM - Khirkh-Ialan, V.; Bakhvalov, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
The analysis of the directions of geoinformation systems use in the military sphere indicates the need to develop domestic simulation systems for combat operations simulation and the creation of a system for a tactical military situation simulation using geoinformation systems for the Armed Forces of Ukraine. The article proposes a conceptual scheme of a system of simulation of a tactical situation on the basis of GIS technologies, which is proposed to be used for planning intelligence and special operations, the definition of objectives, the analysis of terrain and the mutual visibility of opposite sides, management of combat.
Keywords: combat simulation system, geoinformation system, geospatial simulations